2003
DOI: 10.1038/sj.npp.1300192
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Behavioral Effects of Cocaine in Heterozygous Brain-Derived Neurotrophic Factor (BDNF) Knockout Mice

Abstract: Brain-derived neurotrophic factor (BDNF) affects the development of brain neurotransmitter systems, including dopamine and serotonin systems that are important for cocaine's rewarding and locomotor stimulatory properties. Human genomic markers within or near the BDNF locus have been linked to or associated with substance abuse. Post-mortem human brain specimens reveal individual differences in the levels of BDNF mRNA and in mRNA splicing patterns. To assess the effects of lifelong alterations in the levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
0
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(121 citation statements)
references
References 39 publications
5
115
0
1
Order By: Relevance
“…Unlike previous studies with this strain (Duan et al, 2003;Kernie et al, 2000) and with forebrain-specific deletion (Monteggia et al, 2004;Monteggia et al, 2006;Rios et al, 2001;Zorner et al, 2003), these mice did not differ in basal locomotor activity but showed enhanced activity in response to ethanol injection. This is in contrast to cocaine sensitivity, where BDNF +/− mice show reduced locomotor effects and decreased conditioned place preference (Hall et al, 2003). The increased consumption of ethanol in haplodeficient mice could be reversed by systemic delivery of TAT-RACK1.…”
Section: Bdnf In Animal Models Of Anxiety Depression and Addictionmentioning
confidence: 89%
See 1 more Smart Citation
“…Unlike previous studies with this strain (Duan et al, 2003;Kernie et al, 2000) and with forebrain-specific deletion (Monteggia et al, 2004;Monteggia et al, 2006;Rios et al, 2001;Zorner et al, 2003), these mice did not differ in basal locomotor activity but showed enhanced activity in response to ethanol injection. This is in contrast to cocaine sensitivity, where BDNF +/− mice show reduced locomotor effects and decreased conditioned place preference (Hall et al, 2003). The increased consumption of ethanol in haplodeficient mice could be reversed by systemic delivery of TAT-RACK1.…”
Section: Bdnf In Animal Models Of Anxiety Depression and Addictionmentioning
confidence: 89%
“…BDNF potentiates psychostimulant-induced increases in DA both acutely and during sensitization (Altar et al, 1994;Pu et al, 2006;Horger et al, 1999). Conditioned place preference in response to psychostimulants is also reduced in BDNF haplodeficient mice (Hall et al, 2003). Amphetamine increases TrkB expression (Meredith and Steiner, 2006) and BDNF participates in the rewarding properties of psychostimulants by potentiating pre and post synaptic activity (Horger et al, 1999).…”
Section: Bdnf In Animal Models Of Anxiety Depression and Addictionmentioning
confidence: 99%
“…Role m In satiety; m water reward (Horger et al, 1999;Kernie et al, 2000;Nakagawa et al, 2003); improvement in glucose metabolism (Tonra et al, 1999;Nakagawa et al, 2000;Ono et al, 2000) m Drug reward (Horger et al, 1999) K BDNF in mesolimbic pathways regulates appetitive behavior (Eisch et al, 2003;Itoh et al, 2004); BDNF within hypothalamus regulates energy balance by enhancing catabolic processes (Xu et al, 2003) K BDNF may play a role in behavioral sensitization to drugs (Guillin et al, 2001) and potentially to palatable food via its dopaminergic and opioidergic (Siuciak et al, 1994;Siuciak et al, 1995) effects Repeated exposure kIn the hippocampus (Molteni et al, 2002;Molteni et al, 2004) m In mesocorticolimbic areas including, hypothalamus (Meredith et al, 2002;Butovsky et al, 2005); m and upregulation of BDNF receptors during withdrawal (Toda et al, 2002;Grimm et al, 2003); incubation of drug craving, accompanied by m in BDNF (Grimm et al, 2003) BDNF gene knockout animals m In food intake and obesity (Lyons et al, 1999;Kernie et al, 2000;Rios et al, 2001;Xu et al, 2003) k Drug reward (Hall et al, 2003;Horger et al, 1999) Orexin m Food intake (Edwards et al, 1999;Harris et al, 2005) Relapse to drug seeking behavior (Harris et al, 2005) Activated by SGAs ( Ibanez-Rojo et al, 1993;Bencherif et al, 2005) are available, though, to extend preclinical palatable food opioid findings to humans. Neuroimaging studies in obese people reported in...…”
Section: Bdnfmentioning
confidence: 99%
“…In addition, BDNF and NT3 potently influence behavioral sensitization to cocaine and the regulation of dopaminergic transmission to the NAc (Martin-Iverson and Altar 1996;Pierce et al 1999). Behavioral studies have shown that heterozygous BDNF knockout throughout the brain delays the development of cocaine sensitization (Horger et al 1999;Messer et al 2000) and attenuates the rewarding effects of cocaine in conditioned-place preference (Hall et al 2003). As BDNF is implicated in synaptic plasticity, primarily through its receptor TrkB (Bibel and Barde 2000;Bonhoeffer 1996;Kryl et al 1999;Patapoutian and Reichardt 2001;Thoenen 2000), BDNF-mediated neuroadaptations in mesolimbic areas are therefore probably involved in the persistent cocaine seeking induced by exposure to drug cues after withdrawal (Lu et al 2004).…”
Section: Introductionmentioning
confidence: 99%